A methodology for evaluating the accuracy of wave field rendering techniques - Canclini, A.; Annibale, Paolo; Antonacci, F.; Sarti, A.; Rabenstein, Rudolf; Tubaro, S. (36th IEEE International Conference on Acoustics, Speech, and Signal Processing, ICASSP 2011, 2011)
In this paper we propose a methodology for assessing the accuracy of techniques of wave field rendering through loudspeaker arrays. In order to measure the rendered wave field we adopt a solution based on a circular harmonic analysis of the sound field captured by a virtual microphone array. As a result of this analysis stage, we are able to compare the target, the theoretical and the measured wave fields, which may differ due to the non-ideality in the loudspeaker array or in the environment that generates some spurious reverberations. Moreover, in order to quantify the error between target, theoretical and measured wave fields, we define some evaluation metrics, based on RMSE and modal analysis of the acquired wave fields. We show some experimental results on real data. © 2011 IEE
Keywords: Loudspeaker array; virtual microphone array; wave field rendering evaluation